Core Standards of the EUBIROD Project - Cunningham, S. G.; Carinci, F.; Brillante, M.; Leese, G. P.; McAlpine, R. R.; Azzopardi, J.; Beck, P.; Bratina, N.; Bocquet, V.; Doggen, K.; Jarosz-Chobot, P. K.; Jecht, M.; Lindblad, U.; Moulton, T.; Metelko, Ž.; Nagy, A.; Olympios, G.; Pruna, S.; Skeie, S.; Storms, F.; Di Iorio, C. T.; Benedetti, M. Massi (Methods of Information in Medicine, 2016)
Background: A set of core diabetes indicators were identified in a clinical review of current evidence for the EUBIROD project. In order to allow accurate comparisons of diabetes indicators, a standardised currency for data storage and aggregation was required. We aimed to define a robust European data dictionary with appropriate clinical definitions that can be used to analyse diabetes outcomes and provide the foundation for data collection from existing electronic health records for diabetes.Methods: Existing clinical datasets used by 15 partner institutions across Europe were collated and common data items analysed for consistency in terms of recording, data definition and units of measurement. Where necessary, data mappings and algorithms were specified in order to allow partners to meet the standard definitions. A series of descriptive elements were created to document metadata for each data item, including recording, consistency, completeness and quality.Results: While datasets varied in terms of consistency, it was possible to create a common standard that could be used by all. The minimum dataset defined 53 data items that were classified according to their feasibility and validity. Mappings and standardised definitions were used to create an electronic directory for diabetes care, providing the foundation for the EUBIROD data analysis repository, also used to implement the diabetes registry and model of care for Cyprus.Conclusions: The development of data dictionaries and standards can be used to improve the quality and comparability of health information. A data dictionary has been developed to be compatible with other existing data sources for diabetes, within and beyond Europe.
Keywords: Data dictionary; standardised definitions; common dataset; interoperability; diabetes